Menakar Label Fundamentalisme Untuk Muslim - Wibisono, Susilo (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
This study was developed referring to the negative connotation in using the word “fundamentalism ” and its using as an individual or group label. The method used in this study were literature review using many literatures about Islam and fundamentalism in any perspectives. Based on psychology perspective, it said that fundamentalism is an individual psychological construct associated with beliefs and individual interpretation of something, such as ideology, nationality, and religion. According to this perspective, this study states religious fundamentalism as an individual psychological construct that chacactherized as an interval variable. Nevertheless, the concept of religious fundamentalism among Muslims in the psychology literatures was conceptualized and constructed without consideration to normative doctrine of Islam. In fact, the concept of fundamentalism was born from the tradition of Christian and still polemical in its definition. By using the simple map of the doctrine of Islam, this study concludes that fundamentalism as a psychological constructs can be divided into two dimensions, namely pathological fundamentalism and non-pathological fundamentalism. This is related to the dimensionality of Islam that contains core dimensions (ushuul) and branch dimentions (furuu).Keywords:fundamentalism, islam, indonesian moslem.